Validação da versão brasileira da Four Habits Coding Scheme: uma escala para avaliação das habilidades de comunicação de estudantes no encontro clínico - Catani, Renata Rodrigues (2021)
Introduction: The Four Habits Coding Scheme (4HCS) is an instrument used to assess the communication skills of students and health professionals in clinical practice. The Portuguese translation of this scale has not been validated in Brazil. Objectives: To validate the 23 items of the 4HCS through the assessment of its psychometric properties, according to the recommendations of the Consensus-based Standards for the selection of health status Measurement INstruments (COSMIN). Methods: Three external observers assessed twelve medical students and twelve medicine residents in real teaching environments. We calculated reliability with ICC, Cronbach's alpha, Fleiss' Kappa's, and Kendall's coefficients. The structural construct validity was calculated using the Spearman correlation with the Jefferson Scale of Empathy (JSE) and the Patient-Practitioner Orientation Scale (PPOS). We performed the hypothesis test validation by comparing the 4HCS scores of students and residents with the Mann-Whitney test. Results: The scale presented good internal consistency (Cronbach's alpha = 0.94), high intraobserver agreement (ICC = 0.76), and low interobserver agreement (Fleiss' Kappa = 0.25; Kendall = 0.036). The correlations between the scores of JSE, PPOS, and 4HCS were weak and not significant (p=0.15). The scale had good discrimination performance between medical students and residents in all habits (p ≤ 0.01). Conclusion: The 4HCS is a valid and reliable instrument and can be used in Brazil to teach and assess the communication skills in health. The 4HCS is an important advance for the teaching and assessment of health communication in Brazil and may be used for comparisons with international studies.